PERAN KEPEMILIKAN ASING. PENGALAMAN ASING, DANKOMPOSISI GENDER TERHADAP PRAKTIKPENGHINDARAN PAJAK DENGAN PENGUNGKAPAN CSRSEBAGAI VARIABEL INTERVENING - Nazhila Delyanarachma Putri (2023)
The realization of tax revenues over the last 5 years has not been able to meet the targets set due to indications that taxpayers are taking action to minimize the tax burden by exploiting loopholes and ambiguity in tax regulations. This research was conducted with the aim of knowing the effect of foreign ownership, foreign experience, and gender composition on tax avoidance through corporate social responsibility. The population of this study is composed of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021, while the sampling method in this study used a purposive sampling method, which then obtained 84 sample companies. The analysis technique used in this study is panel data regression, and to find the indirect effect, used the causal step mediation regression method with the help of the STATA 13 application. The results of this study indicate that foreign ownership, foreign experience, gender composition, and CSR disclosure have no significant effect on tax avoidance. However, foreign ownership has a significant positive impact on CSR disclosure. In addition, foreign experience and gender composition have no significant effect on CSR disclosure. And CSR disclosure cannot mediate the effect of foreign ownership, foreign experience, and gender composition on tax avoidance.